Measuring Hate among University Students - Hassan, Haider Fadel (Al-Adab Journal, 2022)
Hatred is formed, nourished and directed by certain individuals or groups against various other individuals and groups. In this regard, the current research aims to build a measure of hatred among university students, measure their level of hatred and identify the differences in their hatred according to the variables of gender and academic specialization. The research sample consisted of (100) male and female students from the University of Baghdad, of both sexes, for the scientific and humanitarian majors. The researcher built the hate scale, which consisted of (20) items. The results of the research showed that there were no differences in hatred among university students according to the variables of gender and academic specialization.